1973
DOI: 10.1128/jb.113.3.1455-1461.1973
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structural Changes of Acetobacter suboxydans During Growth in a Defined Medium

Abstract: Cytological differences were observed between stationary-and exponentialphase cells of Acetobacter suboxydans grown in a defined medium. Unstained cells observed with the light microscope just after entering the stationary phase differed from exponentially growing cells in that the former exhibited localized increases in density, particularly in the polar regions. Electron microscopy of thin sections revealed that early stationary-phase cells possessed predominantly polar complexes of intracytoplasmic membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0
1

Year Published

1976
1976
2001
2001

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…Our previously published data (3,7) together with that published here show that (i) the intra- The optimum pH of 5.0 is low compared with that which is reportedly optimum for growth (pH 6.0). However, this bacterium is known to readily initiate growth at pH 4.5 (10), indicating that the optimum pH for sorbitol oxidation is well within the physiological range for this acidtolerant bacterium.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Our previously published data (3,7) together with that published here show that (i) the intra- The optimum pH of 5.0 is low compared with that which is reportedly optimum for growth (pH 6.0). However, this bacterium is known to readily initiate growth at pH 4.5 (10), indicating that the optimum pH for sorbitol oxidation is well within the physiological range for this acidtolerant bacterium.…”
Section: Discussionsupporting
confidence: 59%
“…For cells to have greater respiration rates at a time when their energy needs were decreasing seemed to contradict the idea that limited oxidation functioned solely for energy generation. We found that this increase in oxidative activity was paralleled by the formation of intracytoplasmic membranes (3,7) and an increase in cellular phospholipids (18). Evidenced from thin sections (7) and qualitative fatty-acid analyses (19) strongly suggested that these intracytoplasmic membranes resulted from continued synthesis and subsequent convolution of the plasma membrane after cell division stopped.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Mesosomes possess long-standing recognition although their function remains obscure (31). Complex intracytoplasmic membrane systems have been described for specialized groups of microorganisms, which include the methaneoxidizing bacteria (6,7), the autotrophic-nitrifying bacteria (42), the photosynthetic Thiorhodaceae and Athiorhodaceae (25), the nitrogenfixing Azotobacter (28,30), Escherichia coli strain Olla (44), and Gluconobacter oxydans (2,5). Recently, intracytoplasmic membrane development in the alkane-oxidizing microorganism Acinetobacter sp.…”
mentioning
confidence: 99%